ANALISA PENGARUH CACAT PRODUK AIR TRAPS PADA SIMULASI INJECTION MOLDING - Mulyana, Irvan Septyan (Asosiasi Dosen Muda Indonesia, 2024)
Injection molding, is a manufacturing process for making plastic components. The plastic material is melted, pressed into a mold, then cooled to become the finished product. Injection molding has the potential for air problems or trapped air affecting the quality of the final product. Test data is obtained from software analysis. The bucket cast test results showed defects in the form of holes or unwanted mold marks due to air trapped in the injection molding process. Injection pressure affects air traps defects. At a pressure of 170 Mpa, 180 Mpa, 190 Mpa at a temperature of 200 °C, there is no significant change in the pressure difference and there are still bubble defects in the product, but it is still within the allowable tolerance limits. Optimizing injection pressure is important to reduce bubble defects in the injection molding process. To overcome the air problem in the injection molding process, several ways that can be done include choosing the right plastic raw materials, optimizing injection pressure, adjusting injection speed, and paying attention to good product design or mold design.